COMPARATIVE PERFORMANCE OF BRASSICA NAPUS AND ERUCA SATIVA UNDER WATER DEFICIT CONDITIONS: AN ASSESSMENT OF SELECTION CRITERIA - Mahmood, Seema; Hussain, Asma; Tabassum, Zakia; Kanwal, Fareeha (Journal of Research (Science), 2004)
The comparative performance of Brassica napus and Eruca sativa was assessed under different water deficit conditions. The study indicated that B. napus and E. sativa exhibited certain morphological and phenological changes in response to drought. Moreover, the responses of species were distinct with respect to their tolerance to different drought regimes. E. sativa appeared to be prone to drought regimes. However, B. napus excelled for growth and yield attributes and appeared to possess certain traits that may be considered for the selection of drought resistance. The better performance of B. napus under water deficit environment signifies its potential for further selection for drought tolerance. Thus cultivar/ lines of the species can be exploited for those areas of the country, which experience extended periods of drought.